Clinical features of chronic heart insufficiencies - Malyk, Nataliia; Vlasenko, O. (sci-conf.com.ua, 2021)
Clinical features of chronic heart insufficiencies
Keywords: chronic heart failure; biochemical blood tests; clinical examination; echocardiography; hypertension; diffuse-dystrophic changes of the myocardium